Field evaluation of natural human odours and the biogent-synthetic lure in trapping Aedes aegypti, vector of dengue and chikungunya viruses in Kenya - Eunice A Owino; Rosemary Sang; Catherine L Sole; Christian Pirk; Charles Mbogo; Baldwyn Torto (Parasites & Vectors, 2014)
Abstract Background Methods currently used in sampling adult Aedes aegypti, the main vector of dengue and chikungunya viruses are limited for effective surveillance of the vector and accurate determination of the extent of virus transmission during outbreaks and inter - epidemic periods. Here, we document the use of natural human skin odours in baited traps to improve sampling of adult Ae. aegypti in two different endemic areas of chikungunya and dengue in Kenya – Kilifi and Busia Counties. The chemistry of the volatiles released from human odours and the Biogent (BG)-commercial lure were also compared. Methods Cotton socks and T-shirts were used to obtain natural human skin volatiles from the feet and trunk of three volunteers (volunteers 1 and 2 in Kilifi and volunteers 2 and 3 in Busia). Using Latin square design, we compared the efficacies of BG sentinel traps baited with carbon dioxide plus (a) no bait, (b) human feet volatiles, (c) human trunk volatiles each against (c) a control (Biogent commercial lure) at the two sites. Coupled gas chromatography-mass spectrometry (GC-MS) was used to identify and compare candidate attractants released by the commercial lure and human odours. Results Ae. aegypti captured in the trap baited with feet odours from volunteer 2 and trunk odours from the same volunteer were significantly higher than in the control trap in Busia and Kilifi respectively, [IRR = 5.63, 95% CI: 1.15 - 28.30, p = 0.030] and [IRR = 3.99, 95% CI: 0.95-16.69, p = 0.049]. At both sites, Ae. aegypti captures in traps baited with either the feet or trunk odours from volunteers 1 and 3 were not significantly different from the control. Major qualitative differences were observed between the chemical profiles of human odours and the commercial BG-lure. Aldehydes, fatty acids and ketones dominated human odour profiles, whereas the BG-lure released mainly hexanoic acid. Conclusions Our results suggest that additional candidate attractants are present in human skin volatiles which can help to improve the efficacy of lures for trapping and surveillance of Ae. aegypti.